Seed Priming Used Coconut Water in Different Concentration and Soaked Periode to Increase Soybean Germination - Wibowo, Anang; Zakia, Aulia; Sufianto (Journal of Tropical Crop Science and Technology, 2021)
Soybean seeds are orthodox seeds that quickly deteriorate, especially if the storage environment conditions are less favorable (sub optimum). Soaking using coconut water can be done to overcome the deterioration of soybean seeds by utilizing vegetable waste. The purpose of this research was to study the effect of concentration and duration of coconut water soaking on the process of soybean seed germination. This research was conducted in January-February 2020, at the Agronomy Laboratory, Agrotechnology Study Program, Faculty of Agriculture-Livestock. The soybean used in the study was the Dena I variety. Factorial Completely Randomized Design (CRD) with 2 factors was used in this study. Factor 1 was coconut water concentration (K0 = 0% Coconut Water Concentration; K1 = 25% Coconut Water